REASONS FOR CANCELLATION OF EYE OPERATION ON THE DAY OF INTENDED SURGERY: A QUALITY IMPROVEMENT PROJECT - AAQIL , B; SIDDIQI, A; NAZNEEN, Z; FAISAL, Z; ZAHID, SA; KHAN, MQ (Biological and Clinical Sciences Research Journal, 2024)
Persistent issues with surgery cancellations lead to strain on the healthcare system, leading to a need for more systematic changes to improve efficiency, resource management, and patient care. Objective: Thus the objective of this audit was to find out the burden of cancelled cases and to find out the reasons for their cancellation in a tertiary care hospital. Methods: This research was conducted from 1st Jan 2023 to 31st Dec 2023. A census was done of all the cases on the OT list during this period. All the data was collected on a structured proforma and analyzed on SPSS 23version Results: Out of the total cases on the OT list, 65(12.47%) cases were canceled. The median age with the interquartile range was 19(50) years. The majority of them were males 39 (60%) while females were 26(40%). In the first cycle, 11(61.1%) of canceled cases were because of medical reasons, 3(16.7%) didn’t turn up, 1(5.6%) had a change in plan, and 3(16.7%) were due to equipment failure. In the 2nd cycle, out of canceled cases, about 21(44.7%) were because of medical reasons, 2(4.3%) didn’t turn up, 23(48.9%) had plan changes, (2.1%) were due to equipment failure with a statistically significant difference between the reasons of the 1st and 2nd cycle (p=0.002). Conclusion: This study concludes that the most common reasons leading to the cancellation of operations were medical, equipment, didn’t turn up, and plan changes. All are avoidable and careful following of the guidelines can significantly result in a reduction of cancellation of cases.